Blood cardiac biomarkers responses are associated with 24 h ultramarathon performance. Issue 6 (June 2019) - Hohl, Rodrigo; Nazário de Rezende, Fernando; Millet, Guillaume Y.; Ribeiro da Mota, Gustavo; Marocolo, Moacir
Abstract: Purpose: Clinical significance of cardiac biomarkers response in ultra-endurance runners are not completely elucidated because events vary in distance/duration and competitors modulate running intensity according to individual running capacity. The aim of this study was to examine the relationship between self-selected exercise intensity with cardiac biomarkers comparing experienced (EXP, N = 11) and novice (NOV, N = 14) runners able to finish a 24h ultramarathon (24UM) with significant differences in performance. Methods: Cardiac biomarkers (i.e. CKMB/totalCK, cTnT and NT-proBNP), inflammatory markers (i.e. leukocytes and CRP) and cortisol were analyzed before and after a 24UM. Results: EXP finished the race with significant ( p < 0.05) longer distance than NOV (158.8 ± 15.8 vs 116.8 ± 10.3 Km). Two-way mixed ANOVA showed significant time × performance level interaction with greater increase of cTnT ( F (1, 23) = 6.18, p = 0.021), NT-proBNP ( F (1, 23) = 9.27, p = 0.006) and cortisol ( F (1, 23) = 5.13, p = 0.03) in the EXP group. CKMB/totalCK ( F (1, 23) = 71.90, p < 0.0001) decreased while leukocytes ( F (1, 23) = 100.06, p < 0.0001) and CRP ( F (1, 23) = 93.37, p < 0.0001) increased in both groups (main effect of time). Correlations were found between 24UM distance and cortisol (r = 0.58; p = 0.002), CKMB (r = 0.47; p = 0.017), cTnT (r = 0.44; p = 0.027) or NT-proBNP (r = 0.56; p = 0.003). Cortisol and NT-proBNP were also significantly correlated (r = 0.51; p = 0.01). Conclusions: Although there is no clear evidence of cardiac risk when comparing cardiac biomarkers levels with clinical cut-off values, cardiac biomarkers are associated with running performance and pituitary-adrenocortical system response. In EXP runners, higher levels of cardiac biomarkers and cortisol suggest a more hemodynamically challenged heart during prolonged endurance exercise.